2013
DOI: 10.1158/1940-6207.capr-12-0427
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus Salivarius REN Inhibits Rat Oral Cancer Induced by 4-Nitroquioline 1-Oxide

Abstract: Despite significant advances in cancer therapy, cancer-related mobility and mortality are still rising. Alternative strategies such as cancer prevention thus become essential. Probiotics represent an emerging option for cancer prevention, but studies are limited to colon cancers. The efficiency of probiotics in the prevention of other cancers and the correlative mechanism remains to be explored. A novel probiotics Lactobacillus salivarius REN (L. salivarius REN) was isolated from centenarians at Bama of China,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 43 publications
(44 reference statements)
1
43
0
Order By: Relevance
“…32 Therefore, combining the knowledge that the presence of host CD24 modulates microbial activity in the oral cavity, and that patients with oral cancer have dysbiosis, it is possible that disruption of the CD24-oral microbiome axis alters cancer development. 33,34 Zhang et al 35 demonstrated that probiotic L. salivarius REN treatment significantly damped 4-NQO-induced oral cancer development in rats; however, the significance of the oral microbiome in 4-NQO-induced oral carcinogenesis has never been addressed in mouse models. Further, due to the known role of bacteria-produced sialidase in disrupting the CD24-Siglec-G/10 connection, we investigated if CD24 deficiency alters intra-oral microflora in a manner that may contribute to oral carcinogenesis.…”
Section: Oral Microbiota Do Not Influence 4-nqo-induced Oral Cancer Pmentioning
confidence: 99%
“…32 Therefore, combining the knowledge that the presence of host CD24 modulates microbial activity in the oral cavity, and that patients with oral cancer have dysbiosis, it is possible that disruption of the CD24-oral microbiome axis alters cancer development. 33,34 Zhang et al 35 demonstrated that probiotic L. salivarius REN treatment significantly damped 4-NQO-induced oral cancer development in rats; however, the significance of the oral microbiome in 4-NQO-induced oral carcinogenesis has never been addressed in mouse models. Further, due to the known role of bacteria-produced sialidase in disrupting the CD24-Siglec-G/10 connection, we investigated if CD24 deficiency alters intra-oral microflora in a manner that may contribute to oral carcinogenesis.…”
Section: Oral Microbiota Do Not Influence 4-nqo-induced Oral Cancer Pmentioning
confidence: 99%
“…It also significantly decreased the expression of proliferating cell nuclear antigen (PCNA), and induced apoptosis in a dose-dependent manner. The findings of this study suggest that probiotics may act as potential agents for oral cancer prevention 55 .…”
Section: Cancermentioning
confidence: 67%
“…This effect was attributed to an increased antioxidant status and decreased expression of oncogenes [98] . The beneficial effects of LAB were also reported in animal models of oral cancer [99] , and skin carcinogenesis [100] .…”
Section: Nutrtion and Breast Cancermentioning
confidence: 84%